2013
DOI: 10.5455/2320-6012.ijrms20131131
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological effects of pesticide-cholopyrifos on kidney in albino rats

Abstract: Background: Histopathological lesions have been widely used as biomarkers for health evaluation of organism exposed to pollutants and can be used as warning symptoms for organism health. There are few reports regarding histomorphological changes in kidney following pesticide chlorpyrifos exposure which has prompted us to undertake this study. Methods: The present study was conducted on 45 inbred adult Wistar albino rats of either sex, weighing 145 – 165 gms. These animals were randomly divided into 3 grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 22 publications
4
14
0
2
Order By: Relevance
“…Such liver damage may arise from the toxic effects of malathion, which disturbs the detoxification mechanisms of the liver. Similar findings to the current observations were reported earlier [30] in kidney tissue of rats administered with chlorpyrifos. The most notable effect of spinosad after subchronic exposure in rats is vacuolar degeneration [19].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Such liver damage may arise from the toxic effects of malathion, which disturbs the detoxification mechanisms of the liver. Similar findings to the current observations were reported earlier [30] in kidney tissue of rats administered with chlorpyrifos. The most notable effect of spinosad after subchronic exposure in rats is vacuolar degeneration [19].…”
Section: Discussionsupporting
confidence: 82%
“…Thus, the biochemical parameter data obtained from this study support this speculation in which malathion-and spinosad-treated rats showed alteration in the activities of AST and ALT. Histopathological lesions have been widely used as biomarkers for the health evaluation of organisms exposed to pollutants [30]. Histopathological biomarker in environmental monitoring is of significant advantage as it permits examining specific target organs which are responsible for vital functions.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread use of OPs by public health and agricultural programs has led to severe environmental pollution [2, 3] that constitutes a significant potential health hazard because of the possibility of the acute or chronic poisoning of humans and animals [4]. …”
Section: Introductionmentioning
confidence: 99%
“…In the present study, several destructive changes were appeared in kidney section under LM and SEM observation as a result of STG treatment. Such destructive changes like parenchymal degeneration, swelling and individualization of tubular epithelial cells, glomerular proliferation, increased cytoplasmic granularity, focal necrosis as well as nuclear degeneration might be resulted from the inability of kidney cells to cope up with toxicant induced functional imbalances as were reported earlier (Benjamin et al, 2005;Rekha et al, 2013). Towards the end of STG exposure, the lumens of collecting tubules were appeared to be precipitated by hyaline cast causing atrophy of tubular cells.…”
Section: Discussionmentioning
confidence: 63%